2020
DOI: 10.1029/2020rs007129
|View full text |Cite
|
Sign up to set email alerts
|

Variation on Solar Wind Parameters and Total Electron Content Over Middle‐ to Low‐Latitude Regions During Intense Geomagnetic Storms

Abstract: Streams of the particle ejected from the Sun and the extreme space weather conditions like storms, high-speed streamers (HSSs), interplanetary coronal mass ejections (ICMEs), corotating interaction regions (CIRs), and interplanetary shocks (IS) termed as geomagnetic storms have massive influence in the climate and components of the Earth's upper atmosphere such as total electron content (TEC). The study of TEC helps to understand variations in ionospheric electron density during geomagnetic storms. Global iono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…The authors also reported a hemispherically asymmetric negative ionospheric storm effect which they explained in terms of the thermospheric wind patterns in the two hemispheres. Recently, Mishra et al (2020) studied vertical total electron content (vTEC) using GPS-derived TEC data in mid to low latitude regions over Indian, Australian, Brazilian, and South African sectors during three different geomagnetic storms including the 2015 St. Patrick's Day storm. They reported GMS-induced TEC perturbations in sectors they studied with higher variations in Brazil and India sectors than South African and Australian regions.…”
mentioning
confidence: 99%
“…The authors also reported a hemispherically asymmetric negative ionospheric storm effect which they explained in terms of the thermospheric wind patterns in the two hemispheres. Recently, Mishra et al (2020) studied vertical total electron content (vTEC) using GPS-derived TEC data in mid to low latitude regions over Indian, Australian, Brazilian, and South African sectors during three different geomagnetic storms including the 2015 St. Patrick's Day storm. They reported GMS-induced TEC perturbations in sectors they studied with higher variations in Brazil and India sectors than South African and Australian regions.…”
mentioning
confidence: 99%
“…Several previous studies have shown that positive ionospheric disturbances in the low and mid‐latitudes are the result of PPEF and equatorward disturbance with the main factor of enhanced thermospheric compositions of normalO/N2 $\mathrm{O}/{\mathrm{N}}_{2}$ ratio (de Jesus et al., 2016; Lissa et al., 2020). However, it should be noted that generally, the ionospheric storm effects result from several disturbance mechanisms depending on the storm phase and the latitudinal position (Balan et al., 2009; Maruyama, 2004; Mishra et al., 2020). The ionospheric storm effects can also be observed in other ionospheric phenomena for example, equatorial plasma bubbles (Tulasi Ram et al., 2015) and low altitude ionospheric storm effects (Lastovicka, 1996), traveling ionospheric disturbances and traveling atmospheric disturbances (TAD) (Habarulema et al., 2015; Scherliess & Fejer, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…e TEC values, which change over time and ought to be evaluated along with their location in space, are the principal factors for solar activity and ionosphere-magnetosphere-Sun interaction [3,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. is essay predicts the TEC values through an artificial neural network model (ANNm) [7,8,[37][38][39][40][41][42][43][44][45] over the superstorms of November 20, 2003 (Dst � -422 nT) and November 08, 2004 (Dst � -374 nT).…”
Section: Introductionmentioning
confidence: 99%